Three dimensional electron microscopy reveals changing axonal and myelin morphology along normal and partially injured optic nerves - Giacci, M.; Bartlett, C.; Huynh, M.; Kilburn, M.; Dunlop, S.; Fitzgerald, Melinda (Nature Publishing Group, 2018)
Following injury to the central nervous system, axons and myelin distinct from the initial injury site undergo changes associated with compromised function. Quantifying such changes is important to understanding the pathophysiology of neurotrauma; however, most studies to date used 2 dimensional (D) electron microscopy to analyse single sections, thereby failing to capture changes along individual axons. We used serial block face scanning electron microscopy (SBF SEM) to undertake 3D reconstruction of axons and myelin, analysing optic nerves from normal uninjured female rats and following partial optic nerve transection. Measures of axon and myelin dimensions were generated by examining 2D images at 5 µm intervals along the 100 µm segments. In both normal and injured animals, changes in axonal diameter, myelin thickness, fiber diameter, G-ratio and percentage myelin decompaction were apparent along the lengths of axons to varying degrees. The range of values for axon diameter along individual reconstructed axons in 3D was similar to the range from 2D datasets, encompassing reported variation in axonal diameter attributed to retinal ganglion cell diversity. 3D electron microscopy analyses have provided the means to demonstrate substantial variability in ultrastructure along the length of individual axons and to improve understanding of the pathophysiology of neurotrauma.